Prognostic significance of the systemic immune inflammation index in patients with metastatic and unresectable pancreatic cancer - Han, Rongshuang; Tian, Zibin; Jiang, Yueping; Guan, Ge; Wang, Xiaowei; Sun, Xueguo; Yu, Yanan; Jing, Xue (Frontiers in Surgery, 2022)
Purpose Systemic inflammatory markers may be predictors of the survival rate of patients with pancreatic cancer (PC). The aim of this work was to investigate the prognostic value of markers, mainly the systemic immune inflammation index (SII), in patients with metastatic and unresectable PC and to explore the relationship between markers and liver metastasis. Methods Records of patients with metastatic and unresectable PC at the Affiliated Hospital of Qingdao University from January 2000 to December 2019 and who were followed until December 2020 were retrospectively analyzed. Clinical data and laboratory indexes were collected, and cut-off values for inflammatory markers were determined using median values. The Cox proportional hazard model was used to analyze the prognostic value of the markers through univariate and multivariate survival analysis. Results All 253 patients met the inclusion criteria, and 102 (42.0%) patients had liver metastasis. The patients were divided into a high SII group and a low SII group, and the cut-off value was 533. In the multivariate analysis, high SII (HR = 2.151; p < 0.001), chemotherapy (HR = 0.546; p < 0.001), lymph node metastasis (HR = 4.053; p < 0.001), and distant metastasis (HR = 1.725; p = 0.001) were independent risk markers of overall survival (OS). The level of markers, mainly SII, PLR and NLR, were higher in patients with liver metastasis. Conclusions A high level of SII is an independent risk factor for short overall survival of patients with metastatic and unresectable PC. Patients with a high level of the inflammatory markers SII, PLR, and NLR, may be more prone to early liver metastasis.